Impossible differential distinguisher analysis of GRANULE and MANTRA algorithm - Xiaonian WU; Yingxin LI; Yongzhuang WEI; Yaping SUN (Tongxin xuebao)
The lightweight block cipher algorithms called GRANULE and MANTRA have a simple structure,fast encryption speed,and they can be easy implemented in software and hardware.Two algorithms are especially suitable for resource-constrained environments.To analyze the security of two algorithms,an automatic search method of impossible differential distinguishers was proposed.Based on the structural characteristics of the GRANALE and MANTRA,the S-box differential characteristics were obtained by analyzing the S-box differential distribution table,and then the idea of intermediate encounter was used to traverse from the difference path obtained from the encryption/decryption direction seperately to select the optimal differential path with probability 0.The analysis results show that there are 144 different 7-round impossible differential distinguishers in the GRANULE,and 52 different 9-round impossible differential distinguishers in the MANTRA.Compared with the existing results,the rounds of the proposed distinguisher is currently the highest.